Gen Z's Reception of Covid-19 Information on Digital Media - Ratri Rizki Kusumalestari; Arba’iyah Satriani; Andalusia Neneng Permatasari; Millenia Anjani; Nova N. Nadifah (MediaTor (Jurnal Komunikasi), 2021)
Qualitative studies regarding the reception or reception of Generation Z on Covid-19 information in Indonesia have not been widely carried out. As a generation that was born and grew up with digital technology that is developing very quickly, Gen Z has different characteristics from other generations. Gen Z's acceptance of information related to Covid-19 is one of the important things to assess regarding their potential role and quantity. This study aims to explore Gen-Z's acceptance of Covid-19 information in digital media with a qualitative approach to reception analysis. Data were obtained through FGDs and in-depth interviews. Research findings show that Gen Z prefers access to information that is fast-paced and practical; have a preference for news that is more relaxed, positive and informative; have adequate information literacy to identify hoaxes and perform fact checks; and has a reading position of negotiation and opposition with diverse behavior, but not hegemony-dominant.  The results of this study contribute to the qualitative data of Gen-Z reception of Covid-19 information among the available quantitative data.